Limiting Factors of Forest Cloves (Syzygium Obtusifolium, L.) Productivity in Latu and Hualoy Villages, Amalatu District, West Seram Regency - Fitria S. Kibas; Andrias I. Latupapua; Adelina Siregar (Faculty of Agriculture, Pattimura University, 2022)
Research on the limiting factors for forest cloves (Syzygium obtusifolium, L.) productivity has been conducted in Latu and Hualoy villages, Amalatu sub-district, West Seram Regency. The results showed that the dominant soil factors that limit the productivity of forest cloves were root growth media condition and erosion hazard. However, there was no appropriate technologies to improve all of limiting factors. Actual and potential land suitability for forest clove was categorized as Marginally Suitable covering an area of 1403.1 Ha (61.2 %) and Not Suitable covering an area of 787.9 Ha (34.3%) without the settlements and roads area. The productivity of forest cloves is still low, ranging from 2,250 kg – 3,750 kg/ha/year.